ATM Service Quality and its Effect on Customer Retention: A Case from Pakistani Banks - Hasan, Ameer; ., Muhammad Irfan Arif; ., Nimra Khan (Information Management and Business Review, 2013)
The concept customer retention has received a considerable attention from a few decades in both areas as academic and industry. In the dynamic market environment, customer retention is seen as much important factor to compete in the market. Banks deals very closely to their customers, find, and fulfill their needs. Due to the technological advancement, banks are offering technology based services to the customers, the aim is to have a competitive advantage in satisfying their customer needs and hence to retain their customers. This research attempts to find the technology based ATM service quality, that how the customer are satisfied with it and hence being retained with the bank. The study will find the factor of ATM service quality that are helpful in retaining the customers. Data was collected from different banks of Pakistan and result depicts that the satisfaction of the bank customers with ATM service quality leads to retain the customer with the bank. Hence, the manger should need to focus on the quality ATM service to their customers, to retain their customers with the Banks.